2018
DOI: 10.1111/imj.14058
|View full text |Cite
|
Sign up to set email alerts
|

Changing landscape of hereditary breast and ovarian cancer germline genetic testing in Australia

Abstract: Federal funding for germline genetic testing in hereditary breast and ovarian cancer (HBOC) was recently introduced. Germline testing for HBOC under Medicare Benefits Schedule items 73296/73297 can be requested by any specialist, whereas the previous state‐ and territory‐funded testing was limited to those operating within a familial cancer service. The impact of this decentralisation of HBOC testing on health and economic outcomes is uncertain, primarily as it has potential to significantly disrupt the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Code-stacking (i.e., use of multiple codes, which are commonly based on the performed laboratory procedures), was applied to reimburse the Mammostrat ® and eXagenBC TM tests, as well as molecular pathology tests in the USA [ 95 , 113 ]. Unit fees were applied to reimburse BRCA1/2 tests in Australia [ 89 ] and codes were usually used to reimburse companion diagnostics in France [ 91 , 109 ]. Molecular diagnostic tests were also reimbursed by incorporating them into existing DRG- and locally and nationally negotiated tariff-based payments (e.g., in EU5 countries: Germany, France, Spain, Italy and UK) [ 14 , 115 , 121 , 123 , 125 , 140 , 142 ], or diagnostic costs were covered by state and hospital budgets or pharmaceutical companies [ 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Code-stacking (i.e., use of multiple codes, which are commonly based on the performed laboratory procedures), was applied to reimburse the Mammostrat ® and eXagenBC TM tests, as well as molecular pathology tests in the USA [ 95 , 113 ]. Unit fees were applied to reimburse BRCA1/2 tests in Australia [ 89 ] and codes were usually used to reimburse companion diagnostics in France [ 91 , 109 ]. Molecular diagnostic tests were also reimbursed by incorporating them into existing DRG- and locally and nationally negotiated tariff-based payments (e.g., in EU5 countries: Germany, France, Spain, Italy and UK) [ 14 , 115 , 121 , 123 , 125 , 140 , 142 ], or diagnostic costs were covered by state and hospital budgets or pharmaceutical companies [ 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…This decentralisation of funding also led to a shift of oversight of testing from FCS to cancer treatment specialists. A potential concern of purely treatment‐focused testing is the loss of intergenerational communication and ongoing follow‐up traditionally fostered by the FCS 4 . An alternate approach initiated was “mainstreaming” 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Standard practice in many hospitals had been for cancer patients potentially eligible for genetic testing to be referred to Familial Cancer Services (FCS) for further assessment and to facilitate testing. 4 Recent development of polyadenosine diphosphate ribose polymerase inhibitors (PARP-I) significantly altered the treatment paradigm. Multiple studies evaluating PARP-I have increasingly shown survival benefit for BRCA1/2 carriers in both advanced and relapsed settings [5][6][7] with overall survival benefit demonstrated in the relapse setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to mainstreaming, access to genetic counselling (GC) services has been through referral to genetics services. In many jurisdictions, medical specialists in oncology can now order a panel of multiple genes to assess for hereditary breast and ovarian cancer (HBOC) [ 10 ] without prior referral to genetic services. Mainstreaming assumes that oncology health professionals will take on the role of pre-test GC for GT.…”
Section: Introductionmentioning
confidence: 99%